A colloidal gold immunochromatographic strip for quantitative detection of azoxystrobin in vegetables. (4th May 2021) - Lin, Lu; Xu, Xinxin; Song, Shanshan; Liu, Liqiang; Kuang, Hua; Wang, Zhengyou; Xu, Chuanlai
Abstract : Develop the immunochromatographic strip assay for rapid on-site screening of azoxystrobin in vegetables. Abstract : In this study, a highly specific and sensitive monoclonal antibody (mAb) against azoxystrobin (AZX) was prepared. Based on this mAb and the use of colloidal gold, an immunochromatographic strip (ICS) was developed to specifically detect AZX in cucumber, tomato, and cabbage samples. For qualitative detection, the cut off value using the ICS was 100 ng mL −1 using the naked eye and results could be seen within 10 min. For quantitative detection, the linear regression equations were obtained using a strip reader and the half maximal inhibitory concentrations (IC50 ) were found to be 4.16, 10.64, and 8.90 ng mL −1 in cucumber, tomato, and cabbage samples, the limit of detections (LODs) were 0.36, 1.03, and 0.92 ng mL −1, and the linear detection ranges (IC20 –IC80 ) were respectively 0.64–21.77, 1.86–65.15, and 1.62–49.26 ng mL −1 . The intra-assay recoveries range from 82.5% to 91.4%, with a coefficient of variation of less than 8.2%, and the inter-assay recoveries range from 81.7% to 92.5%, with the coefficient of variation less than 10.2%. The results demonstrated that the ICS could be used as a rapid tool for the qualitative and quantitative detection of AZX in vegetable samples.